A method to remove chattering alarms using median filters. (February 2018) - Sun, Yongkui; Tan, Wen; Chen, Tongwen
Abstract: Chattering alarms are the most found nuisance alarms that will probably reduce the usability and result in a confidence crisis of alarm systems for industrial plants. This paper addresses the chattering alarm reduction using median filters. Two rules are formulated to design the window size of median filters. If the alarm probability is estimated using process data, one rule is based on the probability of alarms to satisfy some requirements on the false alarm rate, or missed alarm rate. If there are only historical alarm data available, the other rule is based on percentage reduction of chattering alarms using alarm duration distribution. Experimental results for industrial cases testify that the proposed method is effective. Highlights: Reduction of chattering alarms via median filters is studied. Two methods to choose the window size of median filters are proposed based on process data and alarm data respectively. Simulation and experimental results for industrial cases testify that the proposed method is effective.